Unobtrusive Measures in Organizational Theory: A Reminder - Webb, Eugene; Weick, Karl E. (Administrative Science Quarterly, 1979)
You know, I am really stupid. For years I have looked for the perfect pencil. I have found very good ones, but never the perfect one. And all the time it was not the pencils but me. A pencil that is all right some days is no good another day. For example, yesterday I used a special pencil soft and fine and it floated over the paper just wonderfully. So this morning I tried the same kind. And they crack on me. Points break and all hell is let loose. This is the day when I am stabbing the paper. So today I need a harder pencil at least for a while. I am using some that are #2 & %. I have my plastic tray you know and in it three kinds of pencils for hard writing days and soft writing days. Only sometimes it changes in the middle of the day, but at least I am equipped for it. I have also some super-soft pencils which I do not use very often because I must feel as delicate as a rose petal to use them. And I am not often that way. But when I do have such moments I am prepared. It is always well to be prepared. Pencils are a great expense to me and I hope you know it. I buy them four dozen at a time. When in my normal writing position the metal of the pencil eraser touches my hand, I retire that pencil (Steinbeck, 1969: 35-36).